STUDY ON DESIGN AND TEST OF FULL LOADING DEVICE WITH AUTOMATIC DISPLACEMENT FOR TURNING CENTERS - HUI Ye; HUANG YuMei; LI Yan (Jixie qiangdu)
In order to simulate the actual cutting situation accurately in measuring stiffness of Numerical Control（ NC）machine tool,a novel full loading method is presented.It is based on the changing of the cutting position as the cutting tool is subject to the action of full load of force and torque under machining process.According to distributing principle of cutting force,a full loading device has been developed through the coordinate transformation of force-bearing point and its direction.The ratio between several forces in various directions is verified by loading tests.Moreover,the device has been applied to stiffness distribution test of NC turning centers,and the displacement of every measured point is obtained when the cutting tool is at different positions.The text results provide referencing data for evaluating and improving construction of machine tool and find application in the prediction and modification of design scheme.